Nanoemulsion-Based Delivery System for Naftifine Hydrochloride: A Promising Approach for Solubility Enhancement - Shinde, Kajal Sunil; Jangme, Chandrapraphu Motichand; Patil, Abhinandan Raosaheb (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: Naftifine hydrochloride, a BCS Class IV antifungal agent, suffers from poor aqueous solubility, limiting its therapeutic efficacy. This study aims to enhance its solubility using a nanoemulsion-based drug delivery system. Materials and Methods: A systematic formulation approach identified oleic acid, Kolliphor® RH40, and Transcutol-P® as optimal components. Pseudo ternary phase diagrams have been utilized to identify and select the optimal emulsification zone and a 3² factorial design optimized the formulation. Results: The nanoemulsion demonstrated improved solubility, thermodynamic stability, and uniform globule size. Conclusion: These results indicate that nanoemulsion technology holds great potential for improving both the solubility and bioavailability of Naftifine hydrochloride for effective topical antifungal therapy.
Keywords: Naftifine hydrochloride; Nanoemulsion; 32 factorial design; Solubility enhancement